Dual contraceptive method use in HIV-serodiscordant Kenyan couples. Issue 4 (10th February 2016) - Roxby, Alison C; Ben-Youssef, Leïla; Marx, Grace; Kinoti, Freda; Bosire, Rose; Guthrie, Brandon; Mackelprang, Romel; Kiarie, James; John-Stewart, Grace; Farquhar, Carey
Abstract : Background: World Health Organization (WHO) guidelines recommend dual contraceptive method use with condoms and another contraceptive to reduce both incidence of HIV/sexually transmitted infection transmission and unintended pregnancies. This qualitative study assessed the barriers to and motivations for dual contraceptive use in Kenyan HIV-serodiscordant couples. Methods: HIV-serodiscordant couples in Nairobi, Kenya, were recruited from two longitudinal cohorts. Qualitative semistructured interviews were conducted using a semistructured questionnaire. Twelve male and 12 female members of serodiscordant couples and 10 women with incident pregnancies during the cohort studies were included. Results: Few couples reported using dual contraceptive methods, with men reporting more condom use than women. No HIV-seropositive men or HIV-seronegative women reported using non-condom contraception. Men and women agreed that men play a dominant role in decisions to use both condoms and contraception in HIV-serodiscordant couples. Participants reported that perceptions of side effects, male partner preference, and reproductive desire were critical factors in contraceptive decisions. Both men and women saw dual contraceptive method use as redundant and a sign of possible unfaithfulness. Many participants actively desired pregnancy, but few were able to accurately define monthly fertility windows. Conclusions: Dual contraceptive method use was low in these HIV-serodiscordant couples, with some couples finding it unnecessary while using condoms, and others being more focused on conceiving a child. Biomedical HIV prevention, including male circumcision, pre-exposure prophylaxis or antiretroviral therapy to reduce HIV transmission, may be more acceptable strategies to promote safer sexual relations among HIV-serodiscordant couples and safer conception when desired.